Nature-based solutions in informal settlements: a systematic review of projects in Southeast Asian and Pacific countries - Wolff, Erich (2023)
Nature-based solutions (NbS) have gained traction in Southeast Asia and the Pacific region over the last decade. While the benefits of NbS are established for most urban contexts, more research is necessary to examine the potential of these solutions in the Global South, particularly in historically disadvantaged contexts such as informal settlements. Responding to this gap, we analyse both grey and academic sources to examine past NbS projects in informal settlements in Southeast Asian and Pacific countries. We identified six main types of NbS that are used to address various social, ecological, and cultural challenges in informal settlements. Some NbS are different from those described in the Global North, ranging from the use of traditional community gardens to enhance food security to the implementation of constructed wetlands as wastewater treatment systems. NbS in the region are often framed as grassroots initiatives spearheaded by local communities or as technical systems implemented within “upgrading programs” delivered by multilateral banks, researchers or international organisations. Analysing the motivations behind these projects, we provide insights into which systems have been used in response to specific needs such as efforts to promote climate adaptation, support food security or compensate residents for disruptions. We outline important social and political implications of the implementation of NbS still understudied in the literature, such as the framing of NbS as “placeholders” for future development or as “compensation” for the disruptions caused by resettlement projects.